Professional and Communicative Activity of Future Psychologist as Linguistic Personality - Kalmykov, Heorhiy (East European Journal of Psycholinguistics, 2015)
The article outlines interrelationship and interdependence of the phenomena “linguistic personality” and “professional speech activity” and the variety of approaches to the description of linguistic personality. By linguistic personality the author means language competence, the availability of linguistic image of the world reflecting the hierarchy of personal values and pragmatic components (goals, motivations, interests, attitudes), etc. Among basic features of a future psychologist are needs and motives, emotions, cognition, knowledge, moral and spiritual, effective and practical, interpersonal and social components. The essence of professional coomunication is revealed through individual discourse activity. It displays ideational and practical, internal and external peculiarities of individual activity. Therefore, communication is viewed as being both personality-centered and socially-centered. The author has also shown the specifics of professional speech activity of future psychologist, its dependence on the types of communication and forms of psychologist’s work, including psychotherapy, psychological prevention, counseling, psycho-diagnostics. References Vygotsky, L. (2000). Mysl i slovo [Thought and word]. Psychology, 462–512. Velichkovsky, B. (2006). Kognitivnaya nauka: Osnovyi psihologii poznaniya [Cognitive Science: Foundations of cognitive psychology]. Moscow: Smysl; Akademiya. Leontyev, A. (1997). Psikhologiya obshcheniya [Psychology of Communication]. Moscow: Smysl. Leontyev, A. (2003 Osnovy psikholingvistiki [Fundamentals of psycholinguistics]. Moscow: Smysl; S.-Petersburg: Lan. Leontyev, A. (1969). Yazyk, rech, rechevaya deyatelnost [Language, speech, vocal activity]. Moskva: Prosveshchenie. Leontyev, A. (1969). Psikholingvisticheskie edinitsy i porozhdenie rechevogo vyskazyvaniya [Psycholinguistic units and producing of vocal statement]. Moscow: Nauka. Rumyantseva, I. (2004). Psikhologiya Rechi i Lingvopedagogicheskaya Psikhologiya [Psychology of Speech and Ligvopedagogical Psychology]. Moscow: Per Se; Logos.